Use of enzyme immunoassays to compare the effect and assess the dosage regimens of three Brazilian Bothrops antivenoms. The Butantan Institute Antivenom Study Group (BIASG). - Theakston, R; Fan, H; Warrell, D; Da Silva, W; Ward, SA; Higashi, H (1992)
The effect of the three main Brazilian polyspecific antivenoms on venom clearance was assessed in 118 moderately envenomed victims of bites by Bothrops species (mainly B. jararaca) in Sao Paulo State, Brazil. Serum samples taken from patients at intervals during their stay in the hospital and at followup approximately four weeks later were tested by enzyme immunoassay for the presence of whole venom and therapeutic antivenom. Results indicated that in patients treated with the standard regimen of either four (40 ml) or eight (80 ml) ampules of each antivenom, venom was cleared from the circulation within four days of antivenom administration. However, high concentrations of antivenom persisted for approximately 10 days and remained detectable until 30-50 days after administration. This suggests that patients may be being treated with excessive amounts of antivenom in Brazil. This practice increases the national cost of antivenom therapy and may contribute to the high frequency of antivenom reactions. Clinically, there was no obvious difference in the efficacy between the three antivenoms.